2017
DOI: 10.1111/jocn.14020
|View full text |Cite
|
Sign up to set email alerts
|

Stuck in tradition‐A qualitative study on barriers for implementation of evidence‐based nutritional care perceived by nursing staff

Abstract: This study contributes with valuable knowledge before the implementation of evidence-based nutritional care. The study provides an understanding of barriers for nutritional care and presents explanations to why nutritional care has failed to become an integrated part of the daily treatment and care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
1
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 36 publications
4
35
1
1
Order By: Relevance
“…This is in line with the findings in another study where healthcare providers in nursing homes experienced that the quality of the psychosocial aspects of the nutritional care was constrained by the demands of routine-driven, task-oriented practices (39) . Lack of time was repeatedly identified as an issue among our participants and is a well-established barrier for quality nutritional care (20,21,40,41) . Studies have reported that healthcare professionals experience a tension between 'person-centredness' and 'the system' because hectic work and structural barriers negatively affect their ability to provide quality person-centred nutritional care (19,20,(39)(40)(41) .…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…This is in line with the findings in another study where healthcare providers in nursing homes experienced that the quality of the psychosocial aspects of the nutritional care was constrained by the demands of routine-driven, task-oriented practices (39) . Lack of time was repeatedly identified as an issue among our participants and is a well-established barrier for quality nutritional care (20,21,40,41) . Studies have reported that healthcare professionals experience a tension between 'person-centredness' and 'the system' because hectic work and structural barriers negatively affect their ability to provide quality person-centred nutritional care (19,20,(39)(40)(41) .…”
Section: Discussionmentioning
confidence: 94%
“…However, moving from rhetoric about person-centred nutritional care in research reports, guidelines and policy documents to actually implementing it in practice appears to be challenging (14,15) . Despite the considerable interest shown in personcentred nutritional care for older persons in recent years (9,11,16,17) , delivery of the care still often lack consideration for the older person's needs and preferences (18)(19)(20)(21) . Problems such as poor communication of nutritional information (18,22) , insufficient knowledge about older person's nutritional needs and lack of attention to their nutritional problems have been described (20,21) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some evidence‐based guidelines and screening protocols are not put in practice if they are considered as a barrier to stop the patient flows (Kirk & Nilsen, ). Other barriers identified in previous studies also included insufficient collaboration between nursing staff and doctors (O′Connell et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that nurses in general considered nutrition important, however, when the nurses ranked providing nutrition care (like serving meals rich in proteins and calories), they found it a less important task (Boaz et al, ). Other studies have explored nurses’ barriers in nutritional care, and nurses explained they lacked time, resources and ward facilities to provide the necessary care (O'Connell et al, ; Papier, Lachter, Hyams, & Chermesh, ). Thus, patient experiences in the current study stress the need for interventions enabling nursing staff to have education about nutrition and how to provide individual counselling and care about nutrition to patients during hospitalisation.…”
Section: Critical Interpretation and Discussionmentioning
confidence: 99%